COVID-19 Pneumonia in Patients on Chronic Hydroxychloroquine Therapy: Three Cases of COVID-19 Pneumonia. (22nd October 2020) - Rahman, Awan K.; Purdy, Adam G.; Ender, Peter T.
Abstract : Hydroxychloroquine has gained popularity as a potential preventative and treatment of COVID-19 pneumonia due to its in vitro activity against the virus. These three cases of COVID-19 pneumonia of varying severities occurred in the setting of chronic hydroxychloroquine use. These cases argue against the use of hydroxychloroquine as a preventative or therapeutic option for COVID-19 pneumonia.